2020
DOI: 10.4155/fmc-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate of Chlorin е 6 With Iron bis(dicarbollide) Nanocluster: Synthesis and Biological Properties

Abstract: Background: Efficiency of both photodynamic and boron-neutron capture (BNCT) anticancer therapies depends on the properties of the used photo- and neutronsensitizer. We report on the synthesis and properties of the advanced photo- and neutronsensitizer designed as a conjugate of chlorin e6 with iron bis(dicarbollide) nanocluster. Results: The conjugate is shown to accumulate efficiently in rat glioblastoma C6 cells delivering >109 boron atoms per cell and thus meeting requirements for BNCT agents, to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Conjugate of chlorin e 6 with iron bis(dicarbollide) nanocluster ( 27 ), a dual sensitizer of BNCT and PDT, was synthesized by the Feofanov group ( Figure 5 A). 163 They found that conjugate 27 accumulated effectively in rat glioblastoma, delivering >10 9 boron atoms per C6 cell (rat glioblastoma C6 cell), which resulted in 50% and 90% of photoinduced cell death with the concentrations of 35 ± 3 and 80 ± 3 nM, respectively. Therefore, this conjugate provided an alternative direction for further research regarding the combination of PDT and BNCT.…”
Section: Applications Of Carboranes As Bnct/photodynamic Therapy Dual Sensitizermentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugate of chlorin e 6 with iron bis(dicarbollide) nanocluster ( 27 ), a dual sensitizer of BNCT and PDT, was synthesized by the Feofanov group ( Figure 5 A). 163 They found that conjugate 27 accumulated effectively in rat glioblastoma, delivering >10 9 boron atoms per C6 cell (rat glioblastoma C6 cell), which resulted in 50% and 90% of photoinduced cell death with the concentrations of 35 ± 3 and 80 ± 3 nM, respectively. Therefore, this conjugate provided an alternative direction for further research regarding the combination of PDT and BNCT.…”
Section: Applications Of Carboranes As Bnct/photodynamic Therapy Dual Sensitizermentioning
confidence: 99%
“…Therefore, this conjugate provided an alternative direction for further research regarding the combination of PDT and BNCT. 163
Figure 5 Synthesis of carborane-derived PDT/BNCT dual sensitizers
…”
Section: Applications Of Carboranes As Bnct/photodynamic Therapy Dual Sensitizermentioning
confidence: 99%
“…Conjugation of closo-dodecaborate and carboranes with different biomolecules (amino acids, peptides, nucleic acid bases, nucleosides, DNA binding molecules, carbohydrates, porphyrins), known drugs, and other tumor-targeting compounds provides a vast diversity of potential low molecular weight boron delivery agents with improved uptake and favorable pharmacokinetic characteristics (Druzina et al, 2016;Barth et al, 2018;Ignatova et al, 2020;Tsurubuchi et al, 2020 and references therein). Monoclonal antibodies, liposomes, polymers, dendrimers, and different types of nanoparticles have been intensively studied as targeted high molecular weight carriers for boron clusters due to the possibility to load them with high 10 B content and to functionalize the surface of constructs with additional tumortargeted ligands (Wu et al, 2006;Calabrese et al, 2012;Laurentia and Rodica, 2016;Barth et al, 2018;Hu et al, 2020 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of BNCT is ensured by a high concentration of 10B atoms in a cancer cell; however, boron clusters themselves do not possess targeting properties. For targeted delivery and the tracking of tumor accumulation, it is promising to use conjugates of boron clusters with photosensitizers (PS), which can be derivatives of natural chlorins [ 8 , 9 , 10 ]. Due to their ability to absorb light in the near infrared region of the spectrum (650–700 nm), chlorin derivatives are widely used in photodynamic therapy (PDT) and fluorescence diagnostics (FD) [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%